Rising direct medical costs of osteoarthritis in Germany from 2002 to 2020: trends, demographic drivers, and public health considerations - Platzer, Hadrian; Gantz, Simone; Färber, Berit; Moradi, Babak (Frontiers in Public Health, 2025)
BackgroundAs a major chronic disease Osteoarthritis (OA) poses a substantial clinical and economic challenge, especially in aging societies. Worldwide the economic burden of OA is significant, however data on related healthcare costs in Germany remain limited. With mounting financial pressures, identifying key cost drivers in healthcare is becoming increasingly vital. This study offers a novel quantification of Germany’s direct medical OA costs, examining demographic trends, and exploring implications for healthcare planning and policy in an international context.MethodsRetrospective analysis of direct medical costs was conducted using data from the German Federal Statistical Office for the years 2002, 2004, 2006, 2008, 2015, and 2020. Costs were stratified by sex, age, and healthcare facility.ResultsIn 2020, diseases of the musculoskeletal system accounted for 10% of Germany’s direct healthcare costs, with osteoarthritis being one of the leading contributors to this economic burden. OA-related costs rose from €8.6 billion in 2015 to €12.1 billion in 2020 (+41%), particularly among older adults. While costs declined in those under 45, they increased by 17% in those aged 45–65, 32% in those aged 65–85, and 99% in those over 85. Inpatient and semi-inpatient costs rose by 32%, reaching €6.6 billion, driven by nursing care, which nearly doubled between 2015 and 2020. Outpatient OA costs totaled €3.4 billion in 2020, with outpatient nursing showing the sharpest rise (+85%). Gender-specific differences were substantial: women incurred 70% of total costs, with higher shares in nursing care, while men had relatively higher expenditures in hospital and rehabilitation settings.ConclusionOsteoarthritis imposes a substantial and rapidly increasing economic burden on the German healthcare system, particularly due to adults aged 65 and older. Inpatient and nursing care have emerged as the primary cost drivers. In a European comparison, Germany ranks among the countries with the highest OA-related direct medical costs. These findings underscore the urgent need for osteoarthritis-specific public health strategies focused on prevention, individualized conservative treatments, and gender-sensitive care models to ensure the long-term sustainability of healthcare systems in aging societies.